DIFFERENCES IN PART OF ANTROPHOLOGICAL STATUS OF PRIMARY SCHOOL MALE STUDENTS IN CENTRAL AND PERIPHERAL CITY AREAS THAT INFLUENCE CHANGES IN PEDAGOGICAL APPROACH TO LESSONS - Faris Rašidagić,; Nermin Nurković,; Dženana Imamović,; Hana Hadžibulić-Nurković, (Sport Scientific And Practical Aspects, 2025)
This research was done to investigate differences of morphological and motoric status of primary school students in central and peripheral city area. This is a continuation of research that was done on female students of same age and same differences in living areas. Research sample is set on purpose and analyses morphological and motoric status of 115 primary school male students in city and suburban areas. There is a clear division in sub sample: 55 students from city area and 60 students from suburban areas. The age of students is between 14 and 15. This research did the analysis of 5 variables in morphological space and 8 variables of motoric space. Variables are in accordance to data evidenced by teachers at the beginning of the school year. After gathering the information, differences were determined by doing T-test for independent samples. T-test results were checked by calculating η 2 values (eta square for independent samples). After that, the aim of research was determined, that is “Differences of morphological and motoric status of primary school male students in central and peripheral city zone”. We can emphasize less fat body in upper extremities, higher capability of keeping the balance and bigger strength in hand grip with students in suburban areas of living. Recommendation: research with same or similar variables should be done on different age categories of both sexes to determine consistency in differences of morphological and motoric status of students in urban and suburban areas